Systemic Characterization of Novel Immune Cell Phenotypes in Recurrent Pregnancy Loss - Liu, Hong; Lin, Xin-Xiu; Huang, Xiao-Bo; Huang, Dong-Hui; Song, Su; Chen, Yang-Jiao; Tang, Jing; Tao, Ding; Yin, Zhi-Nan; Mor, Gil; Liao, Ai-Hua (Frontiers in Immunology, 2021)
Recurrent pregnancy loss (RPL) is a disturbing disease in women, and 50% of RPL is reported to be associated with immune dysfunction. Most previous studies of RPL focused mainly on the relationship between RPL and either T cells or natural killer (NK) cells in peripheral blood and the decidua; few studies presented the systemic profiles of the peripheral immune cell subsets in RPL women. Herein, we simultaneously detected 63 immune cell phenotypes in the peripheral blood from nonpregnant women (NPW), women with a history of normal pregnancy (NP) and women with a history of RPL (RPL) by multi-parameter flow cytometry. The results demonstrated that the percentages of naïve CD4+ T cells, central memory CD4+ T cells, naïve CD8+ T cells, mature NK cells, Vδ1+ T cells and the ratio of Vδ1+ T cells/Vδ2+ T cells were significantly higher in the RPL group than those in the NPW and NP groups, whereas the percentages of terminal differentiated CD4+ T cells, effective memory CD4+ T cells, immature NK cells and Vδ2+ T cells were significantly lower in the RPL group than those in the NPW and NP groups. Interestingly, we found that peripheral T helper (TPH) cells were more abundant in the NPW group than in the NP and RPL groups. In addition, we also determined the 5th percentile lower limit and 95th percentile upper limit of the significantly changed immunological parameters based on the files of the NPW group. Taken together, this is the first study to simultaneously characterize the multiple immune cell subsets in the peripheral blood at a relatively large scale in RPL, which might provide a global readout of the immune status for clinicians to identify clinically-relevant immune disorders and guide them to make clear and individualized advice and treatment plans.